2010
DOI: 10.1167/iovs.09-4494
|View full text |Cite
|
Sign up to set email alerts
|

The Psychometric Validity of the NEI VFQ-25 for Use in a Low-Vision Population

Abstract: The native NEI VFQ-25 is a better performing instrument when split into visual functioning and socioemotional scales. These scales possess valid parameters for assessment of the impact of low vision in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
141
1
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(162 citation statements)
references
References 27 publications
12
141
1
8
Order By: Relevance
“…The NEI VFQ-25 had been used in previous clinical studies (16) (18). However, despite these limitations, the questionnaire was found superior to other tools in assessing vision related quality of life (19) and it was the visual functioning and socioemotional traits that came out as most relevant in this survey.…”
Section: Discussionmentioning
confidence: 95%
“…The NEI VFQ-25 had been used in previous clinical studies (16) (18). However, despite these limitations, the questionnaire was found superior to other tools in assessing vision related quality of life (19) and it was the visual functioning and socioemotional traits that came out as most relevant in this survey.…”
Section: Discussionmentioning
confidence: 95%
“…Other investigators convincingly demonstrated by using modern psychometric techniques that the original tool should be adapted and revalidated. 41,56 The TSS-IOP pops up as the highest quality instrument to assess side effects across different topical treatments, 48,49 yet might be improved as well using Rasch-analysis. If interested in assessing adherence with eye drop treatment, both the adherence questionnaire of Schwartz et al and the EDSQ should be improved, given that both intend to predict nonadherence, but that the discrimination between adherent and nonadherent patients remains difficult.…”
Section: Eyementioning
confidence: 99%
“…Despite being one of the most widely used of the visual function instruments, even the 25-item National Eye Institute Visual Function Questionnaire (NEI VFQ-25) is still not applicable to all patient subsets. 21 In summary, this study has demonstrated that surgical correction of brow ptosis results in a measurable increase in health-related QoL. It has also shown that selfreported preoperative functional impairment is the only outcome measure significantly (and strongly) associated with postoperative increase in functional status, and that visual fields are the best available preoperative objective measure for estimating the expected extent of such improvement.…”
Section: Discussionmentioning
confidence: 60%